Development and reproduction of spider mites Tetranychus turkestani (Acari: Tetranychidae) under water deficit condition in soybeans - Nikolova, Ivelina; Georgieva, Natalia; Naydenova, Jordanka (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
One of the major pests of soybeans in Bulgaria is the spider mite Tetranychus turkestaniUg et Nik (Acari: Tetranychidae) and different results have been reported about the impact of water stress on its development and reproduction. Soybean plants exposed to natural infestation by spider mites, water deficit and treatment with imidacloprid were examined under greenhouse conditions at the Institute of Forage Crops, Pleven, Bulgaria, over the period 2011-2012. The development of mites and their eggs was faster when plants were exposed to water deficit, which created favorable conditions for high density and reproduction of T. turkestani. There was a vertical distribution of protonymphs, deutonymphs and adults as their numbers and egg counts were significantly higher under conditions of water deficit on the upper and middle plant parts, compared with their bottom parts, and imidacloprid treatment had a stronger and more prolonged activity against mites, compared to its influence on well-watered plants. Spider mites on water-stressed plants caused a 24.8% reduction in the contents of plastid pigments, and carotenoids, and 21.5% decrease on well-watered plants.
Keywords: Spider mites; Imidacloprid; Soybeans; Water; Reproduction